Increasing Stakeholder Capacity Field Disaster and Environment in Subtraction Risk Disasters and Conservation Environment - Evi Widowati; Liftiah Liftiah; Ervando Tommy Al-Hanif; Imam Santosa Ciptaning Wahyu; Siti Asiah; Kusuma Wijayanti; Mawardi Hulinggi; Laura Marulia Subroto (Universitas Negeri Semarang, 2024)
Indonesia is a country that has vulnerability high disaster. This matter No regardless from condition geographical. Apart from being prone to natural disasters, in Indonesia there are also many non-natural disasters (due to human behavior). Therefore, Human Resources (HR) who manage disasters in Indonesia must always have updated knowledge and skills related to comprehensive disaster mitigation in order to have adequate capacity and competence. The aim of this service is to map the need to increase personal knowledge specifically in the field of disasters and society in general while increasing their understanding regarding disaster mitigation. The method for collecting data for this activity is through discussions in the form of a Disaster and Environmental Management Seminar Based on Education for Sustainable Development (ESD). The results of this activity showed that 93.8% of participants stated that the characteristics that are generally needed and should be facilitated in higher education include: systematic analysis; risk assessment capabilities; public policy understanding: data analysis skills; inter-sector collaboration; advocacy skills; ability to design policies; understanding of system strengths and weaknesses; social and environmental awareness; and the ability to resolve conflict and tension”.